A NARRATIVE REVIEW ON ANALYSIS OF CHROMOSOMAL ANOMALIES FREQUENCY AND VARIETIES IN PHENOTYPICALLY FEMALE PATIENTS EXPERIENCING AMENORRHEA. - Hussain, Seeba (Student's Journal of Health Research Africa, 2024)
Amenorrhea, characterized by the absence of menstrual periods, affects a significant portion of the female population, signaling potential underlying genetic, anatomical, or hormonal disorders. Chromosomal abnormalities are pivotal in understanding the etiology of amenorrhea, especially in phenotypically female patients experiencing primary or secondary forms of the condition. The review aims to analyze and synthesize research findings on the frequency and types of chromosomal abnormalities in phenotypic females with amenorrhea, highlighting the correlation between specific chromosomal anomalies and the manifestation of amenorrhea. Studies across India have underscored the importance of cytogenetic analysis in diagnosing and managing amenorrhea, revealing a diverse range of chromosomal abnormalities contributing to this condition. Key findings include the necessity of cytogenetic analysis for accurate diagnosis and management, the clinical utility of karyotyping in primary amenorrhea cases, and the broad spectrum of genetic variations contributing to amenorrhea. The review suggests directions for future research, emphasizing the need for improved diagnostic approaches and therapeutic strategies. Understanding the genetic underpinnings of amenorrhea is crucial for developing personalized medicine approaches, optimizing hormone replacement therapy, and employing assisted reproductive technologies based on the patient's genetic and hormonal profile. The findings advocate for the integration of cytogenetic analysis into the standard diagnostic workflow for amenorrhea, enhancing patient care through precise identification of chromosomal abnormalities and informed management strategies.